Tax related behaviour and corporate responsibility - Morris, Gregory (2013)
Many companies engage in behaviour that is intended to reduce, mitigate or avoid the amount of taxation that would otherwise be due. This behaviour may result in changes to the tax code of a country and in comments being made and actions undertaken by governments, academics and other interested parties.